Time Course and Association of Functional and Biochemical Markers in Severe Semitendinosus Damage Following Intensive Eccentric Leg Curls: Differences between and within Subjects - Carmona, Gerard; Mendiguchía, Jurdan; Alomar, Xavier; Padullés, Josep M.; Serrano, David; Nescolarde, Lexa; Rodas, Gil; Cussó, Roser; Balius, Ramón; Cadefau, Joan A. (Frontiers in Physiology, 2018)
Purpose: To investigate the extent and evolution of hamstring muscle damage caused by an intensive bout of eccentric leg curls (ELCs) by (1) assessing the time course and association of different indirect markers of muscle damage such as changes in the force-generating capacity (FGC), functional magnetic resonance (fMRI), and serum muscle enzyme levels and (2) analyzing differences in the degree of hamstring muscle damage between and within subjects (limb-to-limb comparison). Methods: Thirteen male participants performed six sets of 10 repetitions of an ELC with each leg. Before and at regular intervals over 7 days after the exercise, FGC was measured with maximal isometric voluntary contraction (MVC). Serum enzyme levels, fMRI transverse relaxation time (T2) and perceived muscle soreness were also assessed and compared against the FGC. Results: Two groups of subjects were identified according to the extent of hamstring muscle damage based on decreased FGC and increased serum enzyme levels: high responders (n = 10, severe muscle damage) and moderate responders (n = 3, moderate muscle damage). In the high responders, fMRI T2 analysis revealed that the semitendinosus (ST) muscle suffered severe damage in the three regions measured (proximal, middle, and distal). The biceps femoris short head (BFsh) muscle was also damaged and there were significant differences in the FGC within subjects in the high responders. Conclusion: FGC and serum enzyme levels measured in 10 of the subjects from the sample were consistent with severe muscle damage. However, the results showed a wide range of peak MVC reductions, reflecting different degrees of damage between subjects (high and moderate responders). fMRI analysis confirmed that the ST was the hamstring muscle most damaged by ELCs, with uniform T2 changes across all the measured sections of this muscle. During intensive ELCs, the ST muscle could suffer an anomalous recruitment pattern due to fatigue and damage, placing an excessive load on the BFsh and causing it to perform a synergistic compensation that leads to structural damage. Finally, T2 and MVC values did not correlate for the leg with the smaller FGC decrease in the hamstring muscles, suggesting that long-lasting increases in T2 signals after FGC markers have returned to baseline values might indicate an adaptive process rather than damage.